Analisis Faktor-Faktor yang Mempengaruhi Kinerja LPD Kecamatan Marga Kabupaten Tabanan Periode 2019-2021 - Apriada, Kadek; Wulandari, Putu Riska; Zeta, I Gede Putu Tangkas (Universitas Tabanan, 2024)
This study aims to test and obtain emitter evidence regarding the effect of Cash Turnover, Credit Growth, Capital Adequacy, Third Parties Fund and Credit Risk on LPD Performance in Marga District, Tabanan Regency for the 2019-2021 period. The population in this study was LPD in Marga District. The samples to be selected based on the purposive sampling method are selection from predetermined criteria, so that a sample of 21 LPDs was obtained in Marga District, Tabanan Regency. The analysis technique used in this study is multiple linear regression analysis using the SPSS (Statistical Product And Service Solution) tool. The results of this study show that Cash Turnover has a effect on LPD Performance. Credit Growth has no effect on LPD Performance. Capital Adequacy has no effect on LPD Performance. Third Parties Fund have no effect on LPD Performance. and Non Performing Loan has no effect on LPD Performance.